The Effect of the Application and Capability of Information and Communication Technology(ICT) on Knowledge-Based Urban Development in Tehran Metropolis - navid ahangari; Shahrbano movsavi; reza shahbaznejad (تحقیقات کاربردی علوم جغرافیایی)
In the era of knowledge, the rapid advancement of information and communication technology (ICT) is considered a crucial factor in addressing the growing environmental, social, and economic challenges in urban areas. Knowledge-based cities, leveraging this technology, are at the forefront of enhancing the quality of life for residents and the efficiency of services towards achieving sustainable urban development. This study aims to explore the potential and application of ICT in knowledge-based urban development. The data analyzed were collected through a survey of 66 experts from the Deputy of Urban Planning in the 22 districts of Tehran Municipality, ensuring theoretical saturation. Structural equation modeling and the partial least squares approach, utilizing SmartPLS3 software, were employed for data analysis. The findings indicate that the variables of ICT application and potential, as well as knowledge-based urban development in Tehran, and their respective components, scored an average ranging from 3.5 to 4.3 on a 5-point Likert scale, suggesting a relatively stable status. Furthermore, the coefficient for the impact of ICT application and potential on knowledge-based urban development exceeded 0.96, confirming the main model of this research. The outcome suggests that investing in research and development of ICT can serve as a solution to overcome the limitations of knowledge-based urban development in the Tehran metropolis.